Influence of Self-Efficacy on Teaching Digital Technology as Perceived by Maritime Education Faculty in the Philippines - Cabaron, Richard R. (Future Science / FSH-PH Publications, 2023)
Teacher efficacy has been positively connected with student outcomes, including achievement, motivation, self-efficacy beliefs, and instructors' tenacity, passion, commitment, and instructional conduct. The researcher conducted the study to determine the maritime education faculty's self-efficacy in teaching digital technology. The researcher used descriptive research to determine the self-efficacy of maritime education faculty in teaching digital technology. The purposive sampling method was utilized considering that the respondents were the maritime education faculty from three (3) Maritime Higher Education Institutions that participated in the study. The statistical tools used in the study were frequency, percentage, standard deviation, mean, and ANOVA. The Maritime education faculty perceived themselves as having self-efficacy that can be experts in teaching digital technology, such as student engagement, instructional techniques, and classroom management. Even though they teach different courses, self-efficacy has no significant difference when classified according to the courses taught. It is highly recommended that the respective schools of the Maritime education faculty that participated in this study should be given more training on classroom management so that their self-efficacy in teaching the subject will remain high. There is also the need for the teachers to have some dialogues and consultations with the parents of their students to encourage them to collaborate with the teachers to see that their children learn their lessons well.